Case report: disappearance of late gadolinium enhancement and full functional recovery in a young patient with SARS-CoV-2 vaccine-related myocarditis - Korosoglou, Grigorios; Nunninger, Peter; Giusca, Sorin (Frontiers in Cardiovascular Medicine, 2022)
Acute myocarditis was recently demonstrated in previously healthy young male patients after receipt of mRNA SARS-CoV-2 vaccines. Herein, we report on a 21-year-old man who presented with acute fatigue, myalgia, and chest pain 2 days after his second SARS-CoV-2 vaccination with BNT162b2. Cardiac magnetic resonance (CMR) showed acute myocarditis, with mildly impaired LV-function and abundant subepicardial late gadolinium enhancement (LGE). Control CMR after 3 months showed full functional recovery and complete disappearance of LGE. The benefits of SARS-CoV-2 vaccination may significantly exceed the very rare and, in this case, fully reversible adverse effects.
Gesehen am 03.02.2023